Artificial intelligence : a modern approach - Russell, Stuart J (Pearson, 2016)
Includes bibliographical references and index.; Artificial Intelligence: A Modern Approach, 3ed offers the most comprehensive, up-to-date introduction to the theory and practice of artificial intelligence. Number one in its field, this textbook is ideal for one or two-semester, undergraduate or graduate-level courses in Artificial Intelligence.